A de novo genome assembly of cultivated Prunus persica cv. 'Sovetskiy'. - Maria Gladysheva-Azgari; Kristina Petrova; Svetlana Tsygankova; Irina Mitrofanova; Anatoliy Smykov; Eugenia Boulygina; Natalia Slobodova; Sergey Rastorguev; Fedor Sharko (PLoS ONE, 2022)
Prunus persica is one of the main stone fruit crops in Crimea and southern Russia. The P. persica genome has recently been sequenced and annotated in good quality. However, for a deeper assessment of the peach genome, it is necessary to include in the research other cultivars that are in the collection of the Nikitsky Botanical Garden. The cultivars of the Nikitsky Botanical Garden are unique and differ from Western European and American ones, as they are derived from cultivars and forms originating from Central Asian, North Caucasian, Transcaucasian and Eastern European countries. In this paper, we present the assembly of the P. persica cv. 'Sovetskiy' genome obtained using Oxford Nanopore long reads and Illumina short reads by hybrid assembly methods. The assembled genome of P. persica cv. 'Sovetskiy' is 206.26 MB in 226 scaffolds, with N50 24 Mb, including 8 chromosomes. It contains 27140 coding genes, 26973 (99.38%) of which are annotated in at least one functional database. More than 36.05% of the genome regions were identified as repeating elements.